2016
DOI: 10.1111/jfs.12334
|View full text |Cite
|
Sign up to set email alerts
|

Diversity study of microbial community in bacon using metagenomic analysis

Abstract: This study is aimed to explore the diversity and dynamics of microorganisms in bacon. The microbes in 36 bacon samples collected from different plots (BC, BL, and BY) and process stages (stage I, II, III, and IV) were investigated by 16S rDNA sequencing. Quality control and operational taxonomic units clustering was performed by Quantitative Insights Into Microbial Ecology software. Total 1,460 representative sequences were identified. The relative abundance of Firmicutes in BC samples was significantly lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
14
1
Order By: Relevance
“…Various species of genus Cupriavidus have been used in biotransformation (Hafuka et al, 2011), and Cupriavidus metalliduran was used in a multi-strain probiotic to enhance feed conversion efficiency and meat quality traits in chickens (Atela et al, 2019). Four other dominant genera (Pseudomonas, Acinetobacter, Brochothrix, and Massilia) in the current study have been found in the spoilage of fermented pork fat, bacon, and fermented fish (Yi et al, 2016;De Mandal et al, 2018). In the current study, the precise function of the bacteria is uncertain.…”
Section: Characteristics and Interaction Of Bacteria In Meat Productsmentioning
confidence: 78%
See 2 more Smart Citations
“…Various species of genus Cupriavidus have been used in biotransformation (Hafuka et al, 2011), and Cupriavidus metalliduran was used in a multi-strain probiotic to enhance feed conversion efficiency and meat quality traits in chickens (Atela et al, 2019). Four other dominant genera (Pseudomonas, Acinetobacter, Brochothrix, and Massilia) in the current study have been found in the spoilage of fermented pork fat, bacon, and fermented fish (Yi et al, 2016;De Mandal et al, 2018). In the current study, the precise function of the bacteria is uncertain.…”
Section: Characteristics and Interaction Of Bacteria In Meat Productsmentioning
confidence: 78%
“…Staphylococcus aureus, the most common species, has been detected in various foods such as poultry, pork, beef, milk, and vegetables, and can cause staphylococcal food poisoning (Ding et al, 2019). Previous study showed that higher abundance of Staphylococcus was found in bacon samples from Yongshun and Longshan Counties in Hunan Province (Yi et al, 2016). Some Staphylococcus spp., such as S. vitulinus, S. xylosus, S. carnosus, and S. equorum can produce nitrosylmyoglobin (Li et al, 2013;Hu et al, 2018).…”
Section: Characteristics and Interaction Of Bacteria In Meat Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the microbial diversity of preserved meats in Hunan Province found that the microorganisms included approximately 20 phyla, among which Firmicutes, Proteobacteria, Cyanobacteria, and Actinobacteria were the dominant phyla. In addition, there were more than 10 microbial genera, among which Staphylococcus , Sphingomonas , Pseudomonas , Enterobacter , and Leuconostoc were the dominant genera ( Yi et al, 2017 ). The lactic acid bacteria in Longxi preserved meat included L. plantarum , Latilactobacillus curvatus ( L. curvatus ), L. sakei , Companilactobacillus alimentarius ( C. alimentarius ), P. pentosaceus , and Leuconostoc mesenteroides ( L. mesenteroides ), of which L. plantarum has strong acid production capacity and is quite tolerant to sodium chloride and sodium nitrite ( Deng et al, 2019 ).…”
Section: Microbial Diversity In Fermented Meat Productsmentioning
confidence: 99%
“…However, the research on traditional Sichuan bacon has rarely been reported in the literature [13], and the bacterial community dynamics are still unknown. Although some strains have been studied intensively in laboratory patterns, the bacterial communities have yet to be completely clarified in fermented meat because of the drawback of the culture-dependent method [10].…”
Section: Introductionmentioning
confidence: 99%